The deposition of Paraguayan president Fernando Lugo and its repercussions in South American regional organizations - Jatobá, Daniel (2018)
In June 2012, the Paraguayan Parliament executed a procedure that removed President Fernando Lugo from office. Since 1993, only two presidents have completed their mandates, Juan Carlos Wasmosy (1993-1998) and Nicanor Duarte Frutos (2003-2008). With the exception of the latter, all elected presidents have faced either successful or attempted coups, mostly organized by the military. In the case of Lugo, South American governments reacted by suspending Paraguay from two regional organizations (Unasur and Mercosur). This article has two main objectives: 01. to provide an interpretation of Fernando Lugo's deposition, in the context of the ongoing instability of Paraguay's democratic regime, as well as other similar cases in South America; and 02. to analyze the regional repercussions of the interruption of Lugo's presidential mandate, in particular the reactions from other South American governments and the ramifications for three Mercosur institutions: the Common Market Council (CMC), the Mercosur Parliament (Parlasur), and the Permanent Review Tribunal (TPR). It is argued that, despite the involvement of the parliamentary and judicial institutions of the bloc in the Paraguayan case, the governments have prevailed in both the suspension and reincorporation of Paraguay to the bloc, reinforcing both the intergovernmental nature of these regional initiatives and the prominence of national executives in regional decision-making.